Meter-Scale Early Diagenesis of Organic Matter Buried Within Deep-Sea Sediments Beneath the Amazon River Plume - Chong, Lauren S.; Berelson, William M.; McManus, James; Rollins, Nick E. (Frontiers in Marine Science, 2018)
Gravity cores and multi-cores were collected from the Demerara Abyssal plain to examine meter-scale downcore features of early diagenesis in the sediments and relate them to the location of the Amazon River plume in the North Atlantic Ocean. At all sites, the oxygen penetration depth, inferred from nitrate and dissolved manganese profiles, was ~10-20 cm and nitrate was depleted within ~50 cm. However, most of the cores also had a secondary nitrate maximum (4-13µM) at ~50 cm, at a location where we observed changes in gradients of dissolved manganese, iron, and ammonium. Although there is spatial heterogeneity in the profile behavior across the study, we do find subtle diagenetic profile patterns that occur in sediments in relation to their position below the Amazon plume. Dissolved silica profiles show an initial increase downcore, but then all show a decrease to depths of 30-100 cm, thereafter concentrations increase. We suggest this zone of silica uptake is due to reverse weathering processes, possibly involving iron oxidation. A semi-lithified iron crust appeared at nearly all sites, and its position is relict, likely an indicator of the transition from glacial to interglacial sediments.